Clinical profile and outcome of children admitted with acute encephalitis syndrome - Adhikari, Arpita; Gajre, Mona; Kothari, Rini; Chaudhari, Nayan; Sangale, Deepali (International Journal of Contemporary Pediatrics, 2020)
Background: Acute encephalitis syndrome (AES) is an important cause of mortality and morbidity in children. We undertook this study for better understanding of clinical profile and outcome of AES in our settings. Methods: It was a prospective observational study. We studied 15 patients of AES admitted in a tertiary care hospital from December 2016 to May 2017. For investigating AES cases, WHO case definition was adopted. Clinically a case of AES is defined as fever or recent history of fever with change in mental status (including confusion, disorientation, coma, or inability to talk) and/or new onset of seizures (excluding simple febrile seizures). Other early clinical findings could include an increase in irritability, somnolence or abnormal behavior greater than that seen with usual febrile illness. We evaluated their clinical characteristics and outcomes at the time of discharge. Results: Fever, altered sensorium, seizures and headache were the most common symptoms observed in this study. Among 15 cases of AES patients, 6 (40%) recovered completely, while 5 (33.33%) cases had neurological sequelae with a wide range of severity varying from mild to severe at the time of discharge, 4 (26.66%) patient died in the hospital. Conclusions: This study offers a description of the present etiology, clinical presentation and short-term outcome of AES. Use of mechanical ventilation, lower Glasgow coma score, and concurrent seizures are predictors for a poor outcome. Reporting and appropriate workup of all cases would strengthen the AES surveillance and help in reducing the morbidity and mortality due to this disorder.